XG dynamic spectrum access field test results. - McHenry, Mark (IEEE Communications magazine)
The XG Radio system uses dynamic spectrum access technology to determine locally unused spectrum, and then operates on these channels without causing interference to existing non-cooperative users. In August 2006 the XG Radio system was field tested at Fort A.P. Hill, Virginia, in the laboratory, and at field locations in Northern Virginia. There were three major test criteria: to cause no harm (avoid interference), to work (form and maintain connected networks), and to add value (efficiently use spectrum). This article defines the test metrics for fulfillment of these criteria, and describes the test results.